SARCOMANIA - Sanjay Kalra; Sourabh Sharma; Amandeep Singh; Nitin Kapoor (Journal of the Pakistan Medical Association, 2026)
Sarcomania can be defined as “an excessive preoccupation with muscle morphology, function and/or strength exhibited by lay persons, their care givers and/or health care professionals.” Sarcomania occurs in younger adults, mostly men, who are fond of body building. It may be precipitated by an insult, real or perceived, to one’s physical or psychosocial health. Sarcomania presents excessive time spent on resistance exercises, with repeated measurement of muscle mass and function.It may lead to abuse of anabolic drugs and muscle injury An extreme variant of sarcomania is sarcomania nervosa. This can be defined as an excessive preoccupation with muscle morphology, function and/or strength, exhibited by lay persons, their care givers and/or health care professionals, which leads to significant dysfunction in personal, social or professional health. Public awareness, as well as sensitization of all health care professionals about sarcomania is of utmost importance. Muscle dysmorphia should be identified and addressed in a timely manner. Keywords: Health education, muscle health, person centred care, sarcopenia, sarcophobia